DIRECTIONS AND MECHANISMS OF INNOVATIVE HIGH-TECH AND ORGANIZATIONAL DEVELOPMENT OF REAL ECONOMY SECTOR (Academic journal Industrial Machine Building Civil Engineering, 2018)
It is given the results of researching problems and prospects of real economy development and its leading sectors of economic activity – industry and construction. It is established the causes of development absence and inefficient functioning of these areas of management. On this basis the direction of innovation and high-tech industrial and organizational development and building complexes of the countr were determined. Modern mechanisms for the implementation of such strategic tasks at the expense creation and progress outrunning of domestic enterprises that are capable to use modern standards and strategic project management, the latest achievements of science, engineering and technology to develop and implement various investment projects and development programs were proposed. It is proved that research results should promote not only the progress of the real economy, industry and construction, but also to increase global living standards in Ukraine.
Keywords: innovation and high-tech development of the real economic sector; industry and construction; strategic and project management